Evaluation of masonry bonds using ultrasonics the Church of Our Lady of the Assumption - Dauis, Bohol - Corsino, Reuel S. Jr
The October 15, 2013 earthquake had destroyed many of the heritage structures in the Philippines, with more fault lines systems being discovered and the fact that the Philippines is in the Pacific Ring of Fire have urged the call for repair and retrofitting of the remaining heritage structures and mostly of them are masonry structures. A sound structural model is necessary for these repairs and retrofitting and it will only be possible if the strength of materials used in the model is close to the real values. This research focuses on determining the mechanical properties of the masonry bonds. The mechanical properties determined in this research can used in structural models to observe the contribution of the bonds against lateral loads and movements. Nondestructive testing is employed because destructive testing on the actual old fragile structures is not recommended due to uncertainties of the effect of these tests and given that the church is a heritage structure, getting permission to core some of it parts may be difficult. Instead, the binder analysis on the destroyed parts of the church are used to fabricate specimens that emulate the masonry bonds in the actual structure. To cover wide range in strength and pulse velocity the researcher used three water-to-binder ratios in the experiments. The pulse velocity was correlated with the compressive stress and to the determined angle of friction and cohesion. The estimated strength of the masonry bond in one of the walls of the church is 1.285 MPa in compression and 1.072 MPa in shear. The results of this research can be verified by coring a good number of samples from the Church of the of Our Lady of the Assumption and doing statistical analysis on the strengths of each data set or modeling the part of church where the sample "dau 3 m 1" was retrieved and simulate loads on it using ANSYS or other simulation programs.